Perlindungan Hukum terhadap Kurir pada Transaksi COD di Jakarta Selatan - Alfito Arifio (Jurnal Hukum Lex Generalis, 2026)
The development of information technology has brought significant changes to commercial activities in Indonesia, particularly through e-commerce. One popular payment method is Cash On Delivery (COD), where buyers pay for goods in cash upon receipt. However, the COD system poses various problems, especially for couriers who are tasked with delivering goods and receiving payments. Couriers often face risks such as order cancellations by buyers, verbal and physical threats and misunderstandings regarding responsibility for product discrepancies. This study aims to identify the legal issues faced by couriers in COD transactions and analyze the legal protections available to couriers in the event of a dispute. The research method used is empirical juridical with a normative and empirical approach that combines the study of legislation and field data collection through questionnaires and interviews with couriers in the South Jakarta area. Legal protection theory is used as the basis for analysis, focusing on the protection of couriers as third parties who are not directly involved in sales and purchase transactions but play an important role in the transaction process. This study analyzes complaints received by couriers in COD transactions from 100 respondents. The most common complaint was order discrepancies (81,6%), followed by damaged goods (9,7%) and unilateral cancellations (8,7%). Couriers are often the first to face complaints even though they are not directly responsible for the product. A total of 77,7% of complaints have been responded to by the marketplace, demonstrating an active response, but there are no specific regulations governing legal protection for couriers in the COD system, causing uncertainty and injustice. This study recommends the establishment of regulations, legal education, complaint mechanisms and social security for couriers. Collaboration between the goverment, business actors and digital platforms is needed to create legal protection and fairness in the e-commerce ecosystem.